Catalog of technical options for fecal sludge management in Bangladesh - Ulrich, Andreas; Ekasanti, Prawisti; Jayathilake, Nilanthi; Taron, Avinandan (CGIAR Research Program on Water, Land and Ecosystems, 2020)
Fecal sludge management (FSM) in rapidly urbanizing contexts requires an integrated approach that spans the full sanitation service chain containment, emptying, transport, treatment, and resource recovery. A variety of containment systems are employed based on population density and treatment standards, including traditional pit latrines, septic tanks, anaerobic baffled reactors (ABRs), sequencing batch reactors (SBRs), and membrane bioreactors (MBRs). Emptying technologies range from manual tools such as the Gulper to mechanical systems including vacuum tugs and diaphragm pumps, often supported by fluidization and dual-pumping techniques to address dense urban conditions and variable sludge characteristics. Transport solutions incorporate both small- and large-capacity vehicles, trailers, and transfer stations, emphasizing adaptability to narrow streets and coordination with collection schedules for cost efficiency. Treatment technologies are selected based on land availability, energy requirements, and operational complexity, and include sand drying beds, pond systems, geobags, modular subsurface systems, UASBs, and thermal processors. Resource recovery strategies such as co-composting and palletization support circular sanitation models by enabling nutrient recycling and compost marketing. Alignment with citywide inclusive sanitation (CWIS) principles and Sustainable Development Goals (SDGs 3, 6, 10, and 11) underscores the need for decentralized, context-specific FSM systems that integrate environmental sustainability with public health and equity outcomes.